Unveiling challenges in real-time PCR strategies for detecting treatment failure: observations from clinical trials on chronic Chagas disease - Schijman, Alejandro G. (Frontiers in Parasitology, 2023)
Chagas disease (CD) caused by Trypanosoma cruzi remains a Neglected Tropical Disease with limited access to diagnosis and treatment, particularly for chronically infected patients. Clinical trials are underway to improve treatment using new drugs or different regimens, and Real-Time PCR is used to assess the parasitological response as a surrogate biomarker. However, PCR-based strategies have limitations due to the complex nature of T. cruzi infection. The parasite exhibits asynchronous replication, different strains and clones, and diverse tissue tropism, making it challenging to determine optimal timeline points for monitoring treatment response. This mini-review explores factors that may affect PCR-based monitoring and summarizes the endpoints used in current clinical trials for detecting treatment failure. Serial sampling and cumulative PCR results may improve sensitivity in detecting parasitemia and treatment failure in these trials. Con formato: Inglés (Reino Unido) Con formato: Fuente: (Predeterminada) +Cuerpo (Calibri), Color de fuente: Automático, Inglés (Reino Unido), Diseño: Claro Con formato: Inglés (Reino Unido) Con formato: Inglés (Reino Unido)